Polydactyl zinc finger proteins: software and hardware for genomes - Barbas, Carlos (Henry Stewart Talks, 2008)
Development of a universal system for gene regulation, A diversity of recognition domains, Phage display, Targeted endogenous gene regulation in cells and organisms, The specificity issue and genome size, Genomic specificity requires polydactyl proteins, Transcription factor libraries: a powerful new strategy, Cutting and pasting genes and genomes, Zinc finger enzymes and designer epigenetic modifications, Zinc finger nucleases: scissors for genome surgery, Recombinases, Gene delivery vehicles